Growth-at-risk and macroprudential policy design - Javier Suárez (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
This paper explores a potential application of the empirical growth-at-risk (GaR) approach to the assessment and design of macroprudential policies. In parallel to the concept of value-at-risk, the GaR of an economy over a given horizon is a low quantile of the distribution of the (projected) GDP growth rate over the same horizon. In contrast to the standard macroeconomic focus on the expected value (and, perhaps, the variance) of aggregate output growth, looking at low quantiles of such growth implies, as in risk management, a focus on the severity of potential adverse outcomes.
Keywords: G01; G20; G28; 330; macroprudential policy; policy stance; growth-at-risk; quantile regressions